Chemical structures of macrocyclic bis(bibenzyls) isolated from liverworts (Hepaticae). Issue 4 (2000) - Asakawa Asakawa, Yoshinori Yoshinori; Toyota Toyota, Masao Masao; Tori Tori, Motoo Motoo; Hashimoto Hashimoto, Toshihiro Toshihiro
Abstract : Liverworts (Hepaticae) produce a number of macrocyclic bis(bibenzyls) which show interesting biological activity and are of very valuable for the chemosystematic study of liverworts. The structural elucidation of these characteristic natural products are reviewed.